Pointwise best coapproximation in the space of Bochner integrable functions - Eyad Abu-Sirhan (Journal of Numerical Analysis and Approximation Theory, 2020)
Let \(X\) be a Banach space, \(G$\) be a closed subset of \(X\), and \((Ω,Σ,μ )\) be a \(σ\)-finite measure space. In this paper we present some results on coproximinality (pointwise coproximinality) of \(L^{p}(μ,G)\), \(1≤ p≤ ∞\), in \(L^{p}(μ,X\).